Balloon Catheter Dilation in Pediatric Chronic Rhinosinusitis: A Meta-analysis. Issue 5 (September 2020) - Patel, Vijay A.; O'Brien, Daniel C.; Ramadan, Jad; Carr, Michele M.
Background: Paranasal sinus balloon catheter dilation (BCD) represents a tool that has been shown to be safe in the management of pediatric chronic rhinosinusitis (pCRS); however, its efficacy compared to standard treatment regimens has not been well established. Objective: The purpose of this meta-analysis was to evaluate the clinical utility of BCD in pCRS. Methods: Articles reporting BCD for pCRS in patients under 18 years of age were identified via the following search terms: sinusitis OR rhinosinusitis AND balloon dilatation OR balloon dilation OR balloon sinuplasty OR sinuplasty AND adolescent OR children OR infant OR pediatric OR toddler. The primary outcome analyzed includes quality of life improvement as measured via Sinus and Nasal Quality of Life Survey (SN-5) or Sino-nasal Outcome Test (SNOT-22) scores. Results: Eighty studies were abstracted; 10 studies were included for final qualitative analysis after dual investigator screening. Three studies described BCD with surgical controls, including adenoidectomy, saline irrigation, or maxillary antrostomy. Noninferiority was not demonstrated (ie, BCD is inferior) in 2 of 3 studies. Pooled analysis utilizing a random effects model revealed a decreased effect size yet no statistically significant difference between BCD and standard operative techniques as measured by quality of life measures ( g  = −0.04, I 2  = 41%). Conclusion: This work highlights a lack of published evidence regarding the role of BCD in pCRS. Two of the 3 included studies demonstrated the inferiority of BCD when compared to other standard surgical interventions, whereas meta-analysis was unable to detect any statistically significant difference between standard treatment regimens. Future scientific investigations are necessary to assess the comparative effectiveness of BCD in pCRS.